THE EFFECT OF TAX PLANNING, CAPITAL INTENSITY AND EARNINGS GROWTH ON EARNINGS MANAGEMENT - Nurhasanah, Nurhasanah; Berkah Subagyo, Muhammad; Uzliawati, Lia (Yayasan Education and Social Center, 2024)
The purpose of this study was to provide strong evidence regarding the effect of tax planning, capital intensity and earnings growth on lab management. a. This type of research is included in quantitative research. The population in this study were all food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2022. The sample in this study was made up of 31 companies using the purposive sampling method. The type of data used is secondary data obtained from www.id.co.id. Data collection techniques using documentation techniques. The analysis used in this research is multiple linear regression analysis. The results of this study are that tax planning has no significant effect on earnings management with a substantial value of 0.311> 0.05, capital intensity has no significant impact on earnings management with a considerable probability value of 0.793> 0.05, and earnings growth has a substantial effect on earnings management with a significant value of 0.011 <0.05.